On Pragmatic Competence: Politeness Strategies used by Acehnese Students - Fera Busfina Zalha (Seumike : Society Progress Journal, 2026)
Pragmatic competence is a fundamental element in social interaction that allows speakers to adapt their messages to specific social and cultural contexts. This study aims to analyze the politeness strategies employed by Acehnese students in academic and social environments and to identify the sociolinguistic factors influencing these strategic choices. Utilizing Brown and Levinson's politeness theory and Leech’s politeness principles, this research explores how the concept of "face" and local wisdom—such as the Peumulia Jamee philosophy—govern speech behavior. A descriptive qualitative method was applied, with data collected through a Discourse Completion Task (DCT), field observations, and semi-structured interviews involving students from various universities in Aceh. The findings indicate that positive politeness strategies are the most prevalent, reflecting values of solidarity and familiarity. Relative power (P), social distance (Q), and the rank of imposition (D) were identified as the primary determinants. Furthermore, the use of Acehnese linguistic markers, specifically proclitics and honorifics, serves as a crucial indicator of politeness. The study concludes that the pragmatic competence of Acehnese students is deeply intertwined with moral integrity and religious values rooted in local culture